KNOWLEDGE BASE MANAGEMENT SYSTEM UNTUK TROUBLESHOOTING COMPUTER PADA CV VINGKA COMPUTER - Usman, Andi Usri; Hardan, Agri Kharisma; Mabrur, Asep (Teknik Informatika Fakultas Ilmu Komputer, 2021)
The Objective of this research is to easier in providing the waiter to the customer if you want to consult about a computer malfunction. The methodology in this research is the Waterfall method and for the method on the application form of the method Forward Chaining which is a method of inference that reasoning from a problem to a solution and Backward Chaining is Adopting the Goal-Driven, starting from the expectation of what will happen (hypothesis) and then look for evidence to support (or opposite) with our expectations. The results obtained from this research is the Knowledge Base Management System For Computer Troubleshooting integrated with the database to support the process of computer malfunction information easily, quickly, and accurately. The conclusion that can be drawn from this program, namely system reduces the Knowledge Base Trouble Shooting, will be help in gave the service to customers, storage has become a single entity, can reduce redundancy or redundancy of the data, can display information a computer malfunction that required so can easier the officer analysis computer damage